Factors Affecting the Success of Antifungal Therapy in TB Patients with Fungal Co-Infection - umi fatma wati; Fahmi Dimas Abdul Aziz; Rasyidin Rumlus (JURNAL FARMASI DAN MAKANAN, 2025)
Tuberculosis is a lung disease caused by Mycobacterium tuberculosis. Antibiotics have a therapeutic effect by attacking infectious organisms and also eliminating other bacteria that are not the cause of the disease, leading to changes in the ecosystem of normal flora, which results in natural disturbances in microbial ecology. An imbalance in the normal flora can lead to the colonization of respiratory fungi, which will attack the mucosa and proliferate. This study aims to identify the factors that influence the success of antifungal therapy in TB patients with fungal co-infection at Dr. Soetomo Regional General Hospital. The design of this study is retrospective, using electronic medical record data with a total sampling technique conducted during the data collection period from January 1 to December 31, 2024. The total sample is 30 patients. Based on the results, the majority of the gender was male with 20 patients (70.0%), and the largest age group was 51-60 years old with 16 patients (53.3%). The most common Body Mass Index was normal in 18 patients (60%). As many as 20 patients (66.7%) had diabetes mellitus. The most common domicile was Surabaya, with 16 patients (53.3%), and 27 patients (90.0%) had a history of smoking. The BTA examination results showed the highest number of BTA-negative cases in 18 patients (60.0%), the highest number of Geneexpert tests with MTB detected as rifampicin-sensitive in 15 patients (50.0%), the highest number of treatment phase in the intensive phase in 19 patients (63.3%), and the highest number of OAT regimens in 4 KDT in 24 patients (80.0%). As many as 27 patients (90.0%) received antibiotic therapy, either single or combination, during their hospitalization, with the longest duration of antibiotic use being 1-13 days for 20 patients (66.7%). The results of positive fungal cultures were found in 16 patients (53.3%), with the longest duration of antifungal administration being < 14 days in 28 patients (93.3%). Based on the univariate data results, there are 5 variables with a p-value < 0.05, namely gender, age, body mass index, disease history, and tuberculosis drug regimen, which means there is a significant relationship with therapy outcomes. Gender affects therapy outcomes with a p-value of 0.049, which is less than α (p < 0.05). Age with a p-value of 0.029, which is less than α (p < 0.05). Body mass index with a p-value of 0.048 is less than α (p < 0.05). History of type 2 diabetes mellitus with a p-value of 0.033 is less than α (p < 0.05). From the analysis of factors influencing the success of antifungal therapy in TB patients with fungal co-infection, the factors are gender, age, body mass index, medical history, and tuberculosis regimen.